Value added tax - Tait, Alan A. (London ; New York : McGraw-Hill, 1972)
This study hopes to clarify some of the issues and potential difficulties, and suggest likely changes in prices, output, efficiency, and the balance of payments. It concentrates on the actual forms of VAT used, their advantages and drawbacks, the changes possible in theory and in practice, and the desirable forms of VAT harmonization.
Includes index.
Includes bibliographical references: p. 169-173.
ne 06/08/2019
Loans
Keywords: Value-added tax